"Why am I like this?" Consumers discuss their causal beliefs and stigma. Issue 3 (3rd July 2017) - Larkings, Josephine S.; Brown, Patricia M.; Scholz, Brett
ABSTRACT: The stigma associated with mental illness has several negative consequences for consumers (e.g., discrimination in employment and accommodation, reduced help-seeking, increased social isolation) and impacts their quality of life. Consumers' beliefs around the causes of mental illness are thought to influence stigma and self-stigma. This study aims to investigate the types of causal beliefs consumers endorse about their own mental illness, mental illness in general, and consumers' beliefs about causes endorsed by the public. Moreover, this study explores the impact that these beliefs have on factors that influence stigma and self-stigma. A thematic framework guided the analysis of semi-structured interviews with 23 consumers who self-identified as having mental illness. Consumers endorsed multiple causes simultaneously and causes differed between their own mental illness, thinking about mental illness in general, and the causal beliefs perceived to be held by the public. The majority of consumers thought that mental illness in general was caused by a combination of biogenetic, psychological, and environmental factors. Consumers endorsed fewer causal beliefs when considering their own mental illness, with all consumers stating that environmental factors contributed to their illness. Consumers thought that the public had a narrower range of causal beliefs and tended to think the public believed personal weakness/choice caused mental illness. Findings extend previous research and show that consumers' causal beliefs may have an impact on several factors (e.g., control and management of illness, self-blame, feelings of responsibility, perceptions towards self) which are thought to influence treatment, recovery, and stigma.